Infrared and Laser Raman Spectra of Polyethylene and its Normal Coordinate Analysis - Mohan, S.; Prabakaran, A.R. (Asian Journal of Chemistry, 2010)
The rates of the dehydrochlorination of 1,1,1-trichloro-2,2-bis-chlorophenylethane (TPE) by base in mixed-organic solvents have been measured over the temperature range 30–50ºC in different mixtures of binary organic solvents (methanol-carbontetrachloride, methanol-isopropanol and isopropanol-dimethylsulphoxide). In all cases the total rate of the reaction follows a second order and the reaction is first order with respect to both the TPE and to the solvoxide ion concentrations. The kinetic parameter is highly responsive to variation in solvent composition. The rates of the reation show a maximum at 0.1 and a minimum at 0.9 methanol mole fraction in methanol-isopropanol and in methanolcarbontetrachloride respectively. While, in isopropanol-dimethylsulphoxide these extrema are not observed. These results have been discussed in the light of solvent polarity parameters and the changing of solvent structure in such mixtures. The influence of solvent variation has been also examined and discussed in terms of changes in the activation parameters ΔH#and ΔS#.